Cases and Steps for Handling Baggage at PT. Gapura Angkasa at Kualanamu International Airport - Merina Krisdayanti Silaban; Amelia Puspa Tamara (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The development of science and technology is currently growing rapidly. The need for a trip is also felt by customers in choosing transportation services that are considered to be able to take their journey to get to their destination quickly. One of them is felt in the world of aviation, both domestic and international flights. However, in flight there are also obstacles, for example, namely passenger baggage, luggage carried by passengers is also not free from various problems. These baggage service deviations can occur when passengers arrive at the final destination station or during post flight services. Therefore the purpose of this study is to find out how the case and baggage handling steps are. The author uses a qualitative method with a descriptive qualitative type where the data is contained in the form of statements or words that describe the results of research in the field. The data analysis technique used is descriptive analysis, namely by explaining the results of the research by presenting them in the form of descriptive sentences with 3 steps, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that cases of baggage deviation that occur are lost/stray baggage, damaged baggage, surplus baggage and pilfered. The steps taken by the lost and found officers are in accordance with the standard operating procedures of PT Gapura Angkasa and the officers use the facilities and infrastructure to make it easier for the lost and found unit officers to carry out their duties. Then the evaluation is carried out, namely passengers can provide an assessment of the performance of lost and found unit officers through a customer feedback form, through this form passengers can fill out all complaints or praise as desired.